A numerical calibration of structure-function transient thermal measurement based on Cauer RC network. (May 2023) - Bai, Kun; Feng, Shiwei; Li, Xuan; Pan, Shijie; Lu, Xiaozhuang; Feng, Zhihong; Zhang, Yamin
Abstract: Structure functions were originally provided by V. Székely et al. as a nondestructive method for analyzing the thermal resistance of each layer. In this paper, we propose a numerical calibration of structure functions based on the Cauer RC network. The numerical calibration has practical physical significance and can be used as feedback to form a closed loop system in conjunction with the structure functions. A 3D finite element transient thermal simulation is analyzed by structure functions with different setting parameters to determine the feasibility of the numerical calibration. Furthermore, this numerical method can be used to obtain the transient thermal resistance of an ideal heat dissipation structure from the results of the transient dual interface measurement (TDIM).